A direct comparison between AML1-ETO and ETO2-GLIS2 leukemia fusion proteins reveals context-dependent binding and regulation of target genes and opposite functions in cell differentiation - Zhang, Yi-Fan; Wang, Xiao-Lin; Xu, Chun-Hui; Liu, Na; Zhang, Ling; Zhang, Yu-Ming; Xie, Yin-Yin; Zhang, Yuan-Liang; Huang, Qiu-Hua; Wang, Lan; Chen, Zhu; Chen, Sai-Juan; et al. (Frontiers in Cell and Developmental Biology, 2022)
The ETO-family transcriptional corepressors, including ETO, ETO2 and MTGR1, are all involved in leukemia-causing chromosomal translocations. In every case, an ETO-family corepressor acquires a DNA-binding domain (DBD) to form a typical transcription factor – the DBD binds to DNA, while the ETO moiety manifests transcriptional activity. A directly comparative study of these “homologous” fusion transcription factors may clarify their similarities and differences in regulating transcription and leukemogenesis. Here, we performed a side-by-side comparison between AML1-ETO and ETO2-GLIS2, the most common fusion proteins in M2- and M7-subtypes of acute myeloid leukemia, respectively, by inducible expression of them in U937 leukemia cells. We found that, although AML1-ETO and ETO2-GLIS2 can use their own DBDs to bind DNA, they share a large proportion of genome-wide binding regions dependent on other cooperative transcription factors, including the ETS-, bZIP- and bHLH-family proteins. AML1-ETO acts as either transcriptional repressor or activator, whereas ETO2-GLIS2 mainly acts as activator. The repressor-versus-activator functions of AML1-ETO might be determined by the abundance of cooperative transcription factors/cofactors on the target genes. Importantly, AML1-ETO and ETO2-GLIS2 differentially regulate key transcription factors in myeloid differentiation including PU.1 and C/EBPbeta. Consequently, AML1-ETO inhibits, but ETO2-GLIS2 facilitates, myeloid differentiation of U937 cells. This function of ETO2-GLIS2 is reminiscent of a similar effect of MLL-AF9 as previously reported. Taken together, this directly comparative study between AML1-ETO and ETO2-GLIS2 in the same cellular context provides insights into context-dependent transcription regulatory mechanisms that may underlie how these seemingly “homologous” fusion transcription factors exert distinct functions to drive different subtypes of leukemia.